Renewable Energy Consumption-Economic Growth Nexus in Italy - Magazzino, Cosimo (International Journal of Energy Economics and Policy, 2017)
This study examines the renewable energy consumption-economic growth nexus in Italy over the period 1970-2007. Results of unit root tests show that all variables are non-stationary in their level form, but stationary in first differences. Cointegration analysis reveals that a single long-run relationship emerges. According to the long-run estimations, if renewable energy consumption increases by 1%, real GDP decreases by 0.23%. The Toda and Yamamoto approach shows that exists a unidirectional causal flow, running from renewable energy consumption to aggregate income, in line with the “growth hypothesis”. Moreover, these results are confirmed by Granger causality tests. FEVDs evidence that the forecast errors in real GDP are mainly due to uncertainty in GDP itself and renewable energy consumption, while the errors in predicting the renewable energy consumption are sensitive to disturbances only in energy equation. Keywords: Renewable energy consumption; economic growth; causality; Italy JEL Classifications: B22; C32; N54; Q43